Chemical synthesis of left arm of Chlamydomonas reinhardtii mitochondrial genome and in vivo functional analysis - Wang, Quan; Luo, Haolin; Zhuang, Jieyi; Li, Xinyi; Huang, Danqiong; Hu, Zhangli; Zhang, Guiying (Frontiers in Microbiology, 2022)
Chlamydomonas reinhardtii is a photosynthetic eukaryote showing great industrial potential. The synthesis and functionalisation of artificial C. reinhardtii genome in vivo not only promote the development of synthetic biology technology, but also support industries that utilize this algae. C. reinhardtii mitochondrial genome is the smallest and simplest among three sets of inside genomes. Herein, we chemically synthesized and assembled a modified left arm (LA) of mitochondrial genome, comprising four restriction site insertions, 22 synonymous substitutions, one gene location shift, partial inter-region deletion, and a resistance gene aph8 insertion, with >92% similarity to the original nucleotides. The synthesized LA was transferred into the respiratory defect strain cc-2654 using biolistic method. Primer pairs amplifying both internal and crossing LA are adopted to identify transformants. Approximately 30% mitochondrial genome was replaced by synthetic LA in transformants, detected by real-time PCR. In vivo activity of LA was verified through western blot. Restored growth under dark condition and increased reproduction rate were observed. Homogenisation attempt, continuous antibiotic stress exposure, to increase the ratio of LA was explored. Several new techniques may improve the synthesis and endo-functionalization of mitochondrial genome, such as nanotube DNA delivery system, mitochondria-directed transcription activator-like effector nuclease (mito-talen) tools, and intelligen sorting system are discussed. To date, this research firstly synthesized a functional mitochondrial genome in living cells. Although further research is needed, it still provide valuable guidance for the synthesis eukaryotic organelle genomes and inspires rational directions for future effort.